OSA screening with the pediatric sleep questionnaire for adolescents undergoing bariatric surgery in teen‐LABS. Issue 11 (15th September 2016) - Ishman, Stacey; Heubi, Christine; Jenkins, Todd; Michalsky, Marc; Simakajornboon, Narong; Inge, Thomas
Abstract : Objective: Obstructive sleep apnea (OSA) is reported in 70% of adolescents who present for bariatric surgery. The Pediatric Sleep Questionnaire (PSQ) was developed to identify children at risk for OSA but is not validated in adolescents with obesity. The aims of this study were: (1) to assess validity of the PSQ to detect OSA and (2) to determine the correlation between anthropometric and polysomnography measurements. Methods: A cross‐sectional assessment of Teen‐Longitudinal Assessment of Bariatric Surgery participants at high risk for OSA was performed. Participants completed an overnight polysomnography, and caregivers completed the PSQ. Results: Forty‐five participants (84% female, 78% Caucasian, mean age = 16.7 ± 1.5 years) were evaluated. Mean BMI was 51.3 ± 7.7 kg/m 2 and mean obstructive apnea‐hypopnea index (oAHI) was 6.1 ± 5.9 events/h. For diagnosis of OSA (oAHI ≥5), the total PSQ score sensitivity, specificity, and positive predictive value (PPV) were 86%, 38%, and 55%, respectively. For snoring >50% of the time, PPV was 84%, sensitivity was 64%, and specificity was 43%. Sagittal abdominal diameter correlated with oAHI and oxygen saturation nadir ( ρ = 0.34, P = 0.027), whereas BMI, neck, and waist circumference correlated with neither. Conclusions: The PSQ demonstrated low specificity, and PPV and the question regarding snoring >50% of the time did not effectively identify OSA. Sagittal abdominal diameter correlated with oAHI and oxygen saturation nadir.